Gedung Pelayanan Publik dan Ruang Kreatif di Sukabumi dengan Pendekatan Arsitektur Neo Vernakular - Adistira, Gagas (Jurnal Arsitektur Wastu Padma, 2024)
The design of the Public Service Mall Building in Sukabumi aims to integrate public service facilities with creative spaces to meet the needs of the community. The two containers have different characters but have similarities as spaces for community visits. Through the Neo Vernacular architectural approach, the building and environmental design is expected to accommodate local architectural values ​​adapted to contemporary technology. The research was carried out by taking a contextual approach to the environment and studying local architecture. From the discussion, the principle of hierarchical division of spatial planning, building roofs and integration of administrative space with creative space can be stated in accordance with Sundanese architectural cosmology.